Use of sentinel practices to obtain data regarding common clinical conditions and presentations in small animal consultations - Robinson, Natalie Jane (2014)
Gathering data on the veterinary caseload will be useful in directing both future research and the veterinary curriculum. Previous studies have used clinical records to gather this data, but the validity of these methods remains unclear. Direct observation has been used to collect similar data in medicine and may be better able to capture the complexities of the consultation. The aim of the study was to determine the common patients, presentations, diagnoses and interventions during small animal veterinary consultations using direct observation.